Comparison and Acculturation of Western Philosophy and Islamic Philosophy - Bagas Wicaksono Boujesta; Ritasya; Didik Himmawan (Konsultan Jurnal Ilmiah Indonesia, 2024)
The word philosophia is formed from two words, namely philos and shopia, each of which has its own meaning. philos or philia means love/interest (love of), while sophia or sophos means wisdom, knowledge, skill. (skill), practical experience, or intelligence. The research method in this article uses qualitative methods. Qualitative methods are methods that focus on in-depth observation, therefore the use of qualitative methods in research can produce a more comprehensive study of a phenomenon. Then this article uses the library study method by collecting data from various sources. This method is a research method from various book and journal sources that refer to various references. Based on the conclusion from our research results that we can understand the similarities between Western and Islamic educational philosophies, both agree that humans have innate traits from birth that determine their development. The differences between Western and Islamic educational philosophies. Western educational philosophy which was influenced by Greek civilization separates religion from science, making it anthropocentric. In contrast, Islamic educational philosophy is theocentric, with a close relationship between religion and education.